The Competence Disparity of Elementary and Secondary Teacher-Education Graduates - Marjon C. Malacapay (Philippine Social Science Journal, 2022)
There has been substantial research undertaken on teacher-education graduates' competence, but disparities in terms of demographic profile, school of origin, and program of study are yet to be explored. Thus, this paper sets out to characterize the competence of elementary and secondary teacher-education graduates as perceived by themselves and their immediate supervisors, using two sets of survey questionnaires adopting the statements from the CHED Memoranda No. 30, s. 2004 and 59, s. 1996. This study was designed following the cross-sectional procedure for the graduates and their immediate supervisors. It utilized mean, standard deviation, the independent sample T-test, the Mann-Whitney U, and the Kruskal-Wallis tests to analyze and present the data. Disparities in critical thinking, creativity, communication, and awareness of relevant issues were evident among BEEd and BSED graduates. Whereas their demographic profile, such as gender, age, and school of origin, have not influenced their competence. It conveys that their demographic profile did not indicate a significant difference in their acquisition of the mandated competencies. Thus, TEIs should exert an effort to enhance the readiness of their pre-service teachers, the BEEd students, to meet the industry's demands.